Improving Psychological Wellbeing and Healthcare Outcomes Through Decentralization of Healthcare Expenditures in Pakistan - Ain, Qurat ul; Xie, Ling; Yousaf, Tahir (Frontiers in Psychology, 2022)
This article contributes to the limited empirical literature on the impact of decentralization on psychological wellbeing by investigating the hypothesis which signifies that shifts toward more fiscal decentralization in health services would be accompanied by improvements in health outcomes. Formulating a conventional public finance model applied to health care, this hypothesis is tested on a panel data of the Pakistan's provinces during the period 1990 to 2015. The empirical underpinning of the article suggested that the economic reforms of 2001 in Pakistan's healthcare sector, through fiscal decentralization, have imposed a substantial and positive influence on the effectiveness of the public policy in improving the healthcare outcomes over the examined period.